Concurrent Mental Health and Substance Use Disorders among Frequent Emergency Department Users in Saskatchewan, Canada. Issue 1 (June 2017) - Orisatoki, Rotimi; Quail, Jacqueline; Osman, Meric; Teare, Gary; Schwandt, Michael; Neudorf, Cory
ABSTRACT: Objective: : Alcohol and illicit drug abuse are major health problems frequently leading to emergency department (ED) admissions. Repeat admissions in patients with mental health and addiction problems are a growing phenomenon and a major public health issue and health system cost in jurisdictions including Saskatchewan. The objective of this study was to examine mental health and substance use disorder within a group of the top five percent of high‐cost emergency room users. Methods: : This was a population‐based retrospective cohort study of 1, 217 individuals, which constitutes 15% of the 8, 095 people who were identified as the most expensive users of the Saskatchewan healthcare system (i.e., top five percent of hospital costs). The cohort included those diagnosed with a mental health problem and co‐occurring substance use disorder who had made at least one ED visit in the 2012–13 fiscal year (April 1, 2012 to March 31, 2013). Results: : Among patients with a primary mental health diagnosis, those with a co‐occurring substance use disorder had a significantly higher mean number of ED visits (mean 5.68; SD 7.13, p<0.0001) than those without a substance use disorder (mean 3.08; SD 5.36 p<0.0001). The number of total ED visits also increased with the number of primary mental health diagnoses. There were correlations between the different categories of mental health diagnosis and substance use disorders as well. Conclusion: : Among patients with a primary mental health diagnosis, a co‐existing substance use disorder diagnosis is associated with higher ED use. There is a need to improve programs to better support mental health and substance use disorder patients in the community, including concomitant management of problems associated with substance abuse. Abstract : Objectif: : L'abus d'alcool et de drogues illicites est un problème de santé majeur qui conduit souvent à des admissions aux services d'urgence (ED). Les admissions répétitives chez les patients atteints de problèmes de santé mentale et de toxicomanie sont un phénomène croissant et un problème majeur de santé publique et des coûts du système de santé dans les juridictions, y compris la Saskatchewan. L'objectif de cette étude était d'examiner la santé mentale et les troubles reliés à la consommation de drogues dans un groupe représentant les cinq pour cent premiers utilisateurs de salles d'urgence à coût très élevé. Méthodologie: : il s'agissait d'une étude de cohorte rétrospective basée sur une population de 1 217 personnes, ce qui représente 15% des 8 095 personnes identifiées comme les utilisateurs les plus onéreux du système de santé de la Saskatchewan (c.‐à‐d. Les cinq premiers pourcent des coûts hospitaliers). La cohorte comprenait ceux qui avaient un problème de santé mentale, un trouble de la toxicomanie et qui avaient fait au moins une visite de l'ED au cours de l'exercice 2012–13 (du 1er avril 2012 au 31 mars 2013). Résultats: : Parmi les patients ayant un diagnostic de santé mentale primaire, ceux ayant un trouble de la consommation de substances coexistant avaient un nombre significativement plus élevé de visites de l'ED (moyenne de 5, 68; SD 7, 13, p <0, 0001) que ceux sans trouble d'utilisation de substances (moyenne de 3, 08, SD 5, 36 p <0, 0001). Le nombre de visites totales d'ED a également augmenté avec le nombre de diagnostics de santé mentale primaire. Il y avait également des corrélations entre les différentes catégories de diagnostic de la santé mentale et les troubles de l'utilisation de substances. Conclusion: les patients présentant un diagnostic de santé mentale primaire ainsi qu'un diagnostic de toxicomanie coexistant sont sujets à une utilisation plus élevée d'ED. Il est nécessaire d'améliorer les programmes pour mieux soutenir les patients atteints de troubles mentaux et de santé mentale dans la communauté, y compris la prise en charge concomitante des problèmes liés à la toxicomanie.